PUBLISH OR PERISH: ANALISIS BIBLIOMETRIKA TERHADAP LITERATUR TENTANG COVID-19 PADA PANGKALAN DATA SITASI GOOGLE CENDIKIA TAHUN 2019 - 2021 - Arwendria, Arwendria (UIN Imam Bonjol Padang, 2021)
ABSTRACT Bibliometric analysis can provide current topic directions and future research trends. This study uses a Google Scholar database on COVID-19 from 2019-2021 which was extracted from the Publish or Perish application in one iteration. To visualize the results of the bibliometric analysis, the VOSviewer application is used. A total of 964 publications on the topic of COVID-19 were identified. Lauer et al, 2020 obtained the highest citations. But X Wang is the most influential researcher in COVID-19 research on the GS database. The most published publications on COVID-19 were MedRxiv (preprint) and the Journal of Microbiology, Immunology, and Infection, while Elsevier ranked the highest (209) as the most publisher. The term that appears the most in the title is